Influence of Patella Position on Soft Tissue Balance and Clinical Outcomes in Patients Undergoing Minimally Invasive Total Knee Arthroplasty, a Randomized Clinical Trial - Liu, Kaiyuan; Liao, Yuxin; Yang, Dong; Xu, Tianyang; Gao, Qiuming; Jiang, Wenwei; Fan, Lin; Zan, Pengfei; Li, Guodong (Frontiers in Surgery, 2022)
Background We hypothesized that subluxating patellar during minimally invasive total knee arthroplasty (MIS-TKA) would affect intraoperative soft tissue balance and postoperative clinical outcome. Methods From December 2018 to May 2020, 189 patients receiving primary MIS-TKA were enrolled. The gap-balance technique was used, with patients randomly assigned to undergo osteotomy and balance of soft tissue with patella reduced (group A; n = 93) or subluxated (group B; n = 96). The gap and varus⁃valgus angle were compared between groups in both extension and flexion position. The gap and varus⁃valgus angle were also compared before and after reducing patellar in group B. Femoral prosthesis rotation, mechanical femoral axis–to–tibial axis angle, Knee Society Score (KSS), visual analogue scale (VAS), and range of motion (ROM) were compared postoperatively between two groups. Follow-up was 12 months. Results The flexion gap and the varus angle were significantly greater (0.4 mm and 0.7 degree) after patella reduction than before reduction, but the extension joint gap and varus angle were comparable before and after patella reduction. The femoral prosthesis tended to be internally rotated (0.65 degree) in group B. ROM and VAS was better in the group A than in group B at 1 month after surgery, but the differences were not significant at 3, 6 and 12 months. KSS was comparable between the groups after surgery. Conclusions During MIS-TKA, as far as possible, soft tissue balance should be achieved with the patella reduced; otherwise, the femoral prosthesis may be installed more internally and, after patella reduction, the flexion gap and varus angle would increase.